A miR-activated hydrogel for the delivery of a pro-chondrogenic microRNA-221 inhibitor as a minimally invasive therapeutic approach for articular cartilage repair - Shan An; Claudio Intini; Donagh O'Shea; James E. Dixon; Yiran Zheng; Fergal J. O'Brien (Materials Today Bio)
Articular cartilage has limited capacity for repair (or for regeneration) under pathological conditions, given its non-vascularized connective tissue structure and low cellular density. Our group has successfully developed an injectable hydrogel for cartilage repair, composed of collagen type I (Col I), collagen type II (Col II), and methacrylated-hyaluronic acid (MeHA), capable of supporting chondrogenic differentiation of mesenchymal stem cells (MSCs) towards articular cartilage-like phenotypes. Recent studies have demonstrated that silencing miR-221 may be an effective approach in promoting improved MSC chondrogenesis. Thus, this study aimed to develop a miR-activated hydrogel capable of offering a more effective and less invasive therapeutic approach to articular cartilage repair by delivering a pro-chondrogenic miR-221 inhibitor to MSCs using our MeHA-Col I/Col II hydrogel. The MeHA-Col I/Col II hydrogel was cast as previously shown and incorporated with cells transfected with miR-221 inhibitor (using a non-viral peptide delivery vector) to produce the miR-activated hydrogel. Down-regulation of miR-221 did not affect cell viability and enhanced MSCs-mediated chondrogenesis, as evidenced by significantly upregulated expression of key pro-chondrogenic articular cartilage genes (COL2A1 and ACAN) without promoting hypertrophic events (RUNX2 and COL10A1). Furthermore, miR-221 down-regulation improved cartilage-like matrix formation in the MeHA-Col I/Col II hydrogel, with significantly higher levels of sulfated glycosaminoglycans (sGAG) and Col II produced by MSCs in the hydrogel. These results provide evidence of the potential of the miR-activated hydrogel as a minimally invasive therapeutic strategy for articular cartilage repair.